Hi asked in Science & MathematicsMathematics · 4 weeks ago

# How do you solve for x in: ln(3)=ln(10)-(0.1)(x)?

Relevance
• 4 weeks ago

Solve just like any equation:

ln(3) = ln(10) - (0.1)(x)

-0.1x = [ln(3) - ln(10)]

x = [ln(3) - ln(10)] / -0.1 = 12.03972804

• stanschim
Lv 7
4 weeks agoReport

I simply subtracted ln(10) from each side and wrote the equation with the terms reversed from the original problem.  Remember, try to isolate the unknown, x, on the left side of the equation when doing algebra.

• Philip
Lv 6
4 weeks ago

ln(3) = ln(10) - (0.1)x, ie. ln(10) - ln(3) = ln(10/3) = (0.1)x. Multiply through

bt 10 getting x = 10ln(10/3) = 10(1.203972804) = 12.0397804.

• Vaman
Lv 7
4 weeks ago

ln(3)=ln(10)-(0.1)(x)?

0.1x = ln 10 -ln 3=ln 10/3

10/3= e^(0.1x) =e^(x/10)

x = 10 ln(10/3)=12.04

• ?
Lv 7
4 weeks ago

ln(3) =  ln(10) - (0.1)(x) ⇒

0.1x = ln 10 - ln 3

.......ln 10 - ln 3

x = ---------------

............0.1

......2.30259 - 1.09861

x = ------------------------

............0.1

x = 12.0398......................ANS